Pre-industrial Canada, 1760-1849 - Cross, Michael S.; Kealey, Gregory S. (Readings in Canadian social history, 1985)
...This volume presents a selection of scholarly articles designed to introduce the student to currents of social change and development in Canada from 1760 to 1849. With contributions by such respected academic writers as Harold Adams Innis, Judith Fingard, and Sylvia Van Kirk, it provides valuable insights into the role of the working class, violence and protest, class conflicts, and the economic structure of a newly developing nation. --Publisher's description
Keywords: 1800-1899; Canada; Canada Conditions sociales 19e siècle; Canada Conditions économiques 19e siècle; Canada Economic conditions 19th century; Canada Social conditions 19th century; Economic history; Social conditions